The Effect of CSR Disclosure and Profitability on Firm Value in Food and Beverage Sub Sector - Marlina Nur Achyani; Rahmawati Rahmawati; Endang Dwi Amperawati (Universitas Pasundan, 2024)
This study aims to obtain empirical evidence related to the effect of Corporate Social Responsibility (CSR) disclosure and profitability on the value of food and beverage subsector companies. The research population is a food and beverage subsector manufacturing company listed on the Indonesia Stock Exchange from 2019 to 2021. This study used a purposive sampling technique in sampling and obtained a sample of 48 companies with a total of 130 observational data. CSR disclosure in research is measured using GRI Standards, and profitability is proxied by Return on Equity (ROE). Firm value is proxied by Tobin's Q with period t + 1, the use of periods in firm value is a novelty in research. The analysis technique used is multiple linear regression analysis. The results showed that CSR disclosure has a significant negative effect on firm value. While profitability has a significant positive effect on firm value. This study contributes to the literature by introducing a temporal perspective in firm value measurement, highlighting the delayed impact of CSR disclosure and profitability on firm performance.